2020
DOI: 10.1038/s41598-020-75860-6
|View full text |Cite
|
Sign up to set email alerts
|

Results of two consecutive treatment protocols in Polish children with acute lymphoblastic leukemia

Abstract: The aim of the study was to retrospectively compare the effectiveness of the ALL IC-BFM 2002 and ALL IC-BFM 2009 protocols and the distribution of risk groups by the two protocols after minimal residual disease (MRD) measurement as well as its impact on survival. We reviewed the medical records of 3248 patients aged 1–18 years with newly diagnosed ALL who were treated in 14 hemato-oncological centers between 2002 and 2018 in Poland. The overall survival (OS) of 1872 children with ALL treated with the ALL IC 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 20 publications
(21 reference statements)
0
17
1
Order By: Relevance
“…The study comprised 373 pediatric patients, aged 0–18 years, with newly‐diagnosed BCP‐ALL. All were treated between 2010 and 2016 according to ALL‐IC BFM 2009 protocol in the 13 clinical centers of the Polish Pediatric Leukemia/Lymphoma Study Group 5 . Patients diagnosed with T‐cell and mature B‐cell ALL, as well as those who carried KMT2A/AFF1 (formerly myeloid/lymphoid or mixed‐lineage leukemia ( MLL)/AF4 ) or Breakpoint Cluster Region ( BCR)/ABL1 rearrangements, were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study comprised 373 pediatric patients, aged 0–18 years, with newly‐diagnosed BCP‐ALL. All were treated between 2010 and 2016 according to ALL‐IC BFM 2009 protocol in the 13 clinical centers of the Polish Pediatric Leukemia/Lymphoma Study Group 5 . Patients diagnosed with T‐cell and mature B‐cell ALL, as well as those who carried KMT2A/AFF1 (formerly myeloid/lymphoid or mixed‐lineage leukemia ( MLL)/AF4 ) or Breakpoint Cluster Region ( BCR)/ABL1 rearrangements, were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…The median age at diagnosis was 4.5 years (IQR: 2.9–7.1) and median follow‐up was 6.7 years (IQR: 5.7–7.4). The allocation of patients to risk groups was based on the criteria stated in the ALL‐IC BFM 2009 protocol 5 . Additionally, patients were allocated among risk groups defined by MRD at day 15 value (MRD15; standard risk group with MRD15 < 0.1% (MRD‐SR), intermediate risk group with 10.0% > MRD15 ≥ 0.1% (MRD‐IR) and high‐risk group with MRD15 ≥ 10.0% (MRD‐HR)).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although current treatment strategies are becoming increasingly successful, the most frequent cause of treatment failure is relapse. Cumulative relapse risk is 9.3-20.6%, and the outcome prognosis after a relapse is poor [6][7][8]. Several studies have clearly demonstrated that minimal residual disease (MRD) also has a crucial predictive role in ALL Ph+ [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Acute lymphoblastic leukemia (ALL) is the most common pediatric malignant disease with an annual incidence of approximately 3.5/100,000 children worldwide; however, the overall 3-year survival rate can be as high as 87% if proper treatment is applied [1,2]. The 2016 modification of the World Health Organization (WHO) classification categories ALL based on recurrent genetic abnormalities which affect the characteristics of the disease and also determine the outcome and therapeutic decisions [3][4][5].…”
Section: Introductionmentioning
confidence: 99%